Investigation of microwave drying on quality attributes, sensory properties and surface structure of bee pollen grains by scanning electron microscopy - Isik, Ayla; Ozdemir, Murat; Doymaz, Ibrahim (SPRINGER HEIDELBERG, 2021)
The primary objective of this work was to investigate microwave drying behaviour of bee pollen grains, and study the effect of microwave drying on quality, physicochemical properties, sensory characteristics and morphological structure of the bee pollen. Bee pollen samples were dried at 180, 360, 540, 720 and 900 W microwave power levels. Drying kinetics of the bee pollen samples during microwave drying were investigated, and protein, fat, ash, carbohydrate, vitamin C, solubility and colour of dried bee pollen samples were evaluated. Scanning electron microscopy (SEM) images of fresh and microwave dried bee pollens were obtained, and their organoleptic properties were evaluated by panellists. Effective moisture diffusivity (D-eff) values ranged from 0.04 x 10(-8) to 1.14 x 10(-8) m(2)/s, and the activation energy (E-a) was found to be 71.68 W/g. Drying time was shortened by 94% when the microwave power level was increased from 180 to 900 W. Protein, fat, total carbohydrates, vitamin C and colour values of bee pollen were affected by the microwave power level. Microwave power level was an important parameter for the colour change. The lowest Delta E value and the highest solubility (%) were obtained for bee pollen microwave dried at 180 W power level. Morphological changes were observed in microwave dried bee pollen grains. By comparing all the physicochemical properties and organoleptic characteristics of microwave dried bee pollens, the bee pollen dried at 180 W microwave power level was found to retain its quality attributes better than the other microwave dried bee pollens.
Keywords: Bee pollen; Colour; Microwave drying; Quality; Scanning electron microscopy; Sensory properties; Engineering